The effect of food deprivation on the rate of sulfamethazine elimination in goats - Abdullah, A.S.; Baggot, J.D. (Kluwer Academic Publishers, 1988)
The disposition kinetics and cumulative urinary excretion of sulfamethazine were compared in goats fed normally (control) and following a 72-hour period of starvation (fasting). The only pharmacokinetic parameter which showed a statistically significant difference between the two groups was the body (systemic) clearance. This decreased from 2.26±0.28 ml/min· kg ( Mathematical expression ±SD, n=6) in the control group to 1.16±0.54 ml/min·kg in the fasting group (p<0.01). Since the apparent volume of distribution was not affected by starvation, the decreased clearance was attributed to slower metabolism of the drug. Because of the analytical method used to measure sulfamethazine concentrations in plasma and urine, no conclusion could be drawn as to whether the rates of hydroxylation or of acetylation, or both metabolic pathways were decreased in the starved condition.